(untitled) (Swiss Medical Weekly, 2014)
Total hip replacement is one of the most successful surgical procedures of the 20th century (World Health Organisation). The success rate is dependent on the chosen endpoint. Evaluation of the outcome in joint replacement surgery has shifted from the revision rate toward patient satisfaction and quality of life. Patient satisfaction is reported to be up to 96% 16 years postoperatively, but the prevalence of groin pain after conventional total hip replacement ranges from 0.4% to 18.3% and activity-limiting thigh pain is still an existing problem linked to the femoral component of uncemented hip replacement in up to 1.9% to 40.9% of cases in some series. The aim of our article is to review the aetiology, diagnostic procedures and treatment of the painful primary total hip replacement. We discuss the most relevant intrinsic and extrinsic aetiological factors responsible for chronic pain after total hip arthroplasty focusing on comparative studies and randomised controlled trials including diagnostics and management. Detailed analysis of history, clinical examination, imaging and laboratory tests are required prior to any revision for painful total hip arthroplasty. Revision surgery without knowing the underlying pathology should be avoided.